Analisis Biaya Operasional Kendaraan (BOK) Angkutan Umum Pedesaan Trayek Letta–Bungi Di Kabupaten Pinrang - Imran Imran; Andi Sulfanita; Hamka Hamka; Adnan Adnan (Jurnal Universal Technic, 2024)
Vehicle Operating Costs (VOC) refer to the expenses incurred by entrepreneurs/ operators in manage public transportation in a year. The ‘Recealed Pteference’ method is used to determine VOC by conducting a survey based on field conditins. This research aims to determinethe VOC on rural public transport on the Letta-Bungi route and compare the applicable transport rates with the VOC analysis results. It also aims to find out how much income is generated by rural public transportation busineses operating on the Letta-Bungi route. The research employs a quantitative survey method and analysis data using formulas, literature, journals and previous research. The analysis of Vehicle Operational Costs (VOC) for rural public transport on Letta-Bungi route in Pinrag Regency was conducted. For an annual mileage of 11,160 km/year and an average speed of 30 km/hour. According to the analiysis, the yearly operating cost of the vehilcs is IDR 232.956.075,- and the Operating Cost per km is IDR 20.874.20,-. The current tariff of IDR 50.000,-/pnp is higher than the calculated tariff of IDR 42.443,-/pnp. The study analysis also shows that the profits obtained by business operators amount to IDR 55.043,925,-/year and IDR 4.932,25,-/km.